Beta-carotene stability during drying and storage of cassava and sweet potato - Nascimento, P. [UNESP]; Fernandes, N. S. [UNESP]; Mauro, M. A. [UNESP]; Kimura, M. [UNESP] (My University, 2009)
The effect of blanching on the β-carotene stability during drying and storage of cassava and sweet potato was evaluated. The orange-fleshed sweet potato showed good retention of β-carotene during the blanching and drying (100% and 96%, respectively), but lower retention (84% and 91%) was observed in cassava. Cassava also showed lower β-carotene stability than sweet potato during the storage of unblanched dried samples. β-Carotene content of dried cassava was reduced from 8.6 μg/g to traces in 20 days of storage while the initial amount of dried sweet potato (463 μg/g) was reduced by about 45% (210 μg/g). Blanching did not affect the β-carotene retention during the drying, but enhanced the stability of this carotenoid during the storage of dried samples at room temperature, especially in cassava. The initial levels of blanched-dried cassava and sweet potato (7.8 and 513 μg/g, respectively) took 70 days to fall by around 50%.
Keywords: Blanching; Carotenoid; Degradation; Dehydration; Retention; Ipomoea batatas; Manihot esculenta